Cellular Encapsulation Enhances Cardiac Repair. Issue 5 (10th October 2013) - Levit, Rebecca D.; Landázuri, Natalia; Phelps, Edward A.; Brown, Milton E.; García, Andrés J.; Davis, Michael E.; Joseph, Giji; Long, Robert; Safley, Susan A.; Suever, Jonathan D.; Lyle, Alicia N.; Weber, Collin J.; et al.
Abstract : Background: Stem cells for cardiac repair have shown promise in preclinical trials, but lower than expected retention, viability, and efficacy. Encapsulation is one potential strategy to increase viable cell retention while facilitating paracrine effects. Methods and Results: Human mesenchymal stem cells (hMSC) were encapsulated in alginate and attached to the heart with a hydrogel patch in a rat myocardial infarction (MI) model. Cells were tracked using bioluminescence (BLI) and cardiac function measured by transthoracic echocardiography (TTE) and cardiac magnetic resonance imaging (CMR). Microvasculature was quantified using von Willebrand factor staining and scar measured by Masson's Trichrome. Post‐MI ejection fraction by CMR was greatly improved in encapsulated hMSC‐treated animals (MI: 34±3%, MI+Gel: 35±3%, MI+Gel+hMSC: 39±2%, MI+Gel+encapsulated hMSC: 56±1%; n=4 per group; P <0.01). Data represent mean±SEM. By TTE, encapsulated hMSC‐treated animals had improved fractional shortening. Longitudinal BLI showed greatest hMSC retention when the cells were encapsulated ( P <0.05). Scar size at 28 days was significantly reduced in encapsulated hMSC‐treated animals (MI: 12±1%, n=8; MI+Gel: 14±2%, n=7; MI+Gel+hMSC: 14±1%, n=7; MI+Gel+encapsulated hMSC: 7±1%, n=6; P <0.05). There was a large increase in microvascular density in the peri‐infarct area (MI: 121±10, n=7; MI+Gel: 153±26, n=5; MI+Gel+hMSC: 198±18, n=7; MI+Gel+encapsulated hMSC: 828±56 vessels/mm 2, n=6; P <0.01). Conclusions: Alginate encapsulation improved retention of hMSCs and facilitated paracrine effects such as increased peri‐infarct microvasculature and decreased scar. Encapsulation of MSCs improved cardiac function post‐MI and represents a new, translatable strategy for optimization of regenerative therapies for cardiovascular diseases.